5-Hydroxymethylfurfural Alleviates Inflammatory Lung Injury by Inhibiting Endoplasmic Reticulum Stress and NLRP3 Inflammasome Activation - Zhang, Hang; Jiang, Zheyi; Shen, Chuanbin; Zou, Han; Zhang, Zhiping; Wang, Kaitao; Bai, Renren; Kang, Yanhua; Ye, Xiang-Yang; Xie, Tian (Frontiers in Cell and Developmental Biology, 2021)
5-Hydroxymethylfurfural (5-HMF) is a common reaction product during heat processing and the preparation of many types of foods and Traditional Chinese Medicine formulations. The aim of this study was to evaluate the protective effect of 5-HMF on endotoxin-induced acute lung injury (ALI) and the underlying mechanisms. Our findings indicate that 5-HMF attenuated lipopolysaccharide (LPS)-induced ALI in mice by mitigating alveolar destruction, neutrophil infiltration and the release of inflammatory cytokines. Furthermore, the activation of macrophages and human monocytes in response to LPS was remarkably suppressed by 5-HMF in vitro through inhibiting the NF-κB signaling pathway, NLRP3 inflammasome activation and endoplasmic reticulum (ER) stress. The inhibitory effect of 5-HMF on NLRP3 inflammasome was reversed by overexpressing ATF4 or CHOP, indicating the involvement of ER stress in the negative regulation of 5-HMF on NLRP3 inflammasome-mediated inflammation. Consistent with this, the ameliorative effect of 5-HMF on in vivo pulmonary dysfunction were reversed by the ER stress inducer tunicamycin. In conclusion, our findings elucidate the anti-inflammatory and protective efficacy of 5-HMF in LPS-induced acute lung injury, and also demonstrate the key mechanism of its action against NLRP3 inflammasome-related inflammatory disorders via the inhibition of ER stress.